(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
Effluents samples collected from post discharge of equalization tanks of local composite textile mills of Saver were treated with aquatic macrophytes, algae and their combination. They were found to be effective for the reduction of chemical oxygen demand (COD) and pH. Sixty nine per cent of COD was reduced with the combination treatment of Nostoc, Eichhornia crassipes and Pistia stratiotes. With the combination treatment of Nostoc and E. crassipes reduced 65 per cent COD in glass containers. pH was reduced from 11.2 to 8.6. Between earthen and glass containers, glass container was found to be more effective. Key words: Industrial effluents; COD; pH; Aquatic macrophytes; Algae DOI: 10.3329/jbas.v34i1.5487 Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 9-14, 2010